EFFECTS OF SAND AND LIVE ROCK BOTTOM ON WATER QUALITY IN AQUARIUM TANK - Hoang, Do Huu; Tram, Dang Tran Tu; Hue, Nguyen Thi Nguyet; Dang, Do Hai (Vietnam Journal of Marine Science and Technology, 2019)
Marine ornamental aquarium is more and more popular. Nowadays, biofiltration system can convert nitrogen from toxic forms (NH4+/NH3, NO2-) into a less toxic form (NO3-), which creates a better water quality for the development of ornamental fishes in aquarium tank. This experiment was carried out to evaluate the efficiency of environmental quality by supplementation of sand and live rock in aquarium tank. There were two treatments with rock and sand supplement to the bottom of the tanks (NT1) and tanks without rock and sand added (NT2). There were 3 replicates for each treatment and the experiments were carried out in ten weeks. Results showed that sand and live rock could improve water quality and play as good place for fish and other creature hiding and reduce the water used. Water temperatures were 28.69oC (NT1) and 28.80oC (NT2), pH was about 8.13, salinity ranged from 34‰ to 35‰ in both treatments. NH4+was 0.035 ± 0.003 mgN/ml in the two treatments. After 2 weeks of putting fish in the experimental tanks NO2- values were 0.023 mgN/l (in treatment NT2) and 0.018 mgN/l (in treatment NT1). The average values of NO2- for whole experimental period in the NT1 and NT2 were 0.008 ± 0.001 mgN/l and 0.010 ± 0.002 mgN/l, respectively (P = 0.061). NO3- values were not significantly different between the two treatments (P > 0.05). However, the ratio of NO2-/NO3- in NT1 was lower compared to this value in NT2 (NT1: 0.15 ± 0.03% and NT2: 0.39 ± 0.09%, P = 0.018). This paper provides an important reference to help aquarists to design and control their ornamental aquarium tank suitably.